Rewilding the boundary : fostering socio-ecological integration, a community conservation and visitor’s centre in Bushbuckridge. - Damon, Hoskin (My University, 2022)
As one of the world’s most biodiverse regions,South Africa possesses an abundance of natural resources including 19 national parks and a multitude of private game reserves. These areas are responsible for safeguarding thousands of indigenous mammal, bird, reptile, amphibian, fish and plant species- many of which have been classified as endangered today.This biodiversity, however, also comes with numerous challenges. Over and above some of our existing and crucial challenges pertaining to unemployment and education, human-wildlife conflict is rife in regions where human presence and natural ecosystems meet. In conserving our abundant natural resources for future generations, it is imperative that our focus shift to the most sustainable drivers of our wildlife and biodiversity economies. Community conservation, ecological restoration and eco-tourism initiatives all offer great socio-economic opportunity to communities located along the fringes of protected ecosystems such as those in Bushbuckridge which border the Greater Kruger National Park, my chosen context. While architecture continues to play a prominent role within the confines of these reserves under the scope of eco-tourism, this role ends at the reserve boundaries. These have, over time, formed a distinct divide between buffer zone communities and the natural resources on their doorstep as well as many of the opportunities they present. Limited benefit sharing and socio-ecological integration has further strengthened perceptions of separation, originating through colonial conservation practices and policies of the past. The research presented in this report explores the existing socio-economic and ecological systems of Bushbuckridge as well as the role a sustainable architectural intervention could play in connecting or reconnecting those living in buffer zone communities to this natural environment, actively facilitating transformation through education, skills development and job creation with a focus on conservation and ecological restoration. Natural ecosystems do not end at the man-made divide and a mutually beneficial symbiotic relationship between people and wildlife is of utmost importance in safeguarding our natural heritage while allowing for sustainable socio-ecological integration.
A research report submitted in partial fulfilment requirement for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, South Africa, 2021